PENGKAJIAN PUISI PENERIMAAN CHAIRIL ANWAR MENGGUNAKAN PENDEKATAN STILISTIKA - Kusmadi Sitohang (Jurnal Membaca Bahasa dan Sastra Indonesia, 2018)
This paper aims to know the use of writing style on the poetry acceptance of the work of Chairil Anwar. Acceptance poems by Chairil Anwar’s analysis with a stylistic approach found the language used by the dominant poet of everyday language and found only one style of language, thas is simile. The use of diction in the poem is classified as a simple diction so as to provide a simple effect for the reader. Rima ussed is very consistent, because each end ofthe line on the poem ends with the letter i. The style of language found by the author is the style simile language.